Santo Antônio: os governantes e a política - Souza, José Antônio de C. R. de (Revista Eclesiástica Brasileira, 2004)
A proximidade de eleições municipais dos brasileiros, dentre os quais um grande número é devoto de Santo Antônio, sugere buscar em Sermões deste santo subsídios que norteiem os formadores de opinião, os governantes, os candidatos e os próprios eleitores para que bem cumpram com seus respectivos deveres. Inspirando-se na Sagrada Escritura e no pensamento filosófico de perfil estóico-agostiniano, o Santo magistralmente nos fala e nos ensina a respeito da justiça, do bem-comum, da paz, da solidariedade, da responsabilidade e do compromisso social, coroados pela Caridade e cuja vivência resulta na construção do Reino nesta terra. Abstract: As the Brazilian municipal elections draw near and because so many Brazilians are devotees of Saint Anthony, this paper suggests that we should turn to the Saint’s Sermons in search of insights that could help public-opinion makers, rulers, candidates and the voters themselves to fulfill their respective duties well. Inspiring himself in the Sacred Scriptures and in a philosophical thought of Stoic-Augustinian nature, and with great mastery, the Saint speaks to us and teaches us about justice, the common good, peace, solidarity, responsibility and social commitment, all crowned by the virtue of Charity and the practice of which can lead to the building of the Kingdom in this earth.